Child Health Outcomes Associated With Early Childhood Exposure Todigital Screen Technologies - P, Dr. Jayakumar; Aniruddhan V.J, Dr. Aryama; R, Dr. Parthasarathy; Priyadharshini, Ms. Gowthami (Adolescência e Saúde, 2026)
Background: The proliferation of smart phones, tablets, televisions, and internet-based media has led to a growing presence of digital screen technologies in early childhood. Digital tools can help with learning and communication, but there are concerns about their effect on children’s physical, cognitive, behavioural and emotional development. Objective: This study aimed to investigate the association between exposure to digital screen technologies in early childhood and a range of child health outcomes including sleep quality, body mass index (BMI), language development, physical activity and behavioural well-being. Methodology: Cross-sectional analysis of data collected from 3200 children aged 0-8 years. Daily screen time, device type, content exposure and parental mediation were collected with parent-reported questionnaires. Child health outcomes were measured by standardized developmental and behavioural measures. Multivariate regression analysis at the 95% confidence level was used to determine the association between screen exposure and health indicators. Findings: Children with >4 hours of screen time per day had lower average sleep duration (9.1 hours/night) than children with <1 hour of screen time (11.2 hours/night). Higher screen exposure was related to higher BMI (20.4 vs 16.2 kg/m2), lower physical activity (4.6 vs 10.8 hours/week) and lower language development scores (75 vs 84). Cognitive performance was improved by educational content in combination with parental involvement. Conclusion: Excessive screen time during early childhood is associated with bad physical, behavioural, and developmental effects, but moderate and educational screen time can have cognitive benefits. The findings underscored the importance of balanced digital media practices and parental guidance in early childhood.